Global humanitarianism and media culture - Lawrence, Michael; Tavernor, Rachel (2019)
This collection interrogates the representation of humanitarian crisis and catastrophe, and the refraction of humanitarian intervention and action, from the mid-twentieth century to the present, across a diverse range of media forms: traditional and contemporary screen media (film, television and online video) as well as newspapers, memoirs, music festivals and social media platforms (such as Facebook, YouTube and Flickr). The book thus explores the historical, cultural and political contexts that have shaped the mediation of humanitarian relationships since the middle of the twentieth century. Together, the chapters illustrate the continuities and connections, as well as the differences, which have characterised the mediatisation of both states of emergency and acts of amelioration. The authors reveal and explore the significant synergies between the humanitarian enterprise, the endeavour to alleviate the suffering of particular groups, and media representations, and their modes of addressing and appealing to specific publics. The chapters consider the ways in which media texts, technologies and practices reflect and shape the shifting moral, political, ethical, rhetorical, ideological and material dimensions of international humanitarian emergency and intervention, and have become integral to the changing relationships between organisations, institutions, governments, individual actors and entire sectors.